Mial (microalgae lipids) - exploitation of microalgae lipidome: a lipidomics strategy to bioprospect bioactive phytochemicals - Conde, Tiago Alexandre Teixeira de Sousa (2024)
The production of food systems can be affected by Climate Change (CC), reducing food accessibility and nutritional quality, which in turn can cause malnutrition and the increase incidence of non-communicable diseases (NCD). Microalgae are potential alternatives as novel food, as they are sustainable and versatile resources, which have been consumed by humans for centuries. Microalgae are rich in essential nutrients tackling nutritional deficits that predispose individuals to NCD and have a wide and diverse set of bioactive phytochemicals providing important health benefits. Polar lipids carrying n-3 polyunsaturated fatty acids (PUFA) are among the algae phytochemicals that have been recently regarded for their bioactive properties, with health-promoting benefits and the potential to prevent NCD. However, the lack of knowledge of the lipidome of microalgae, the absence of studies on the structural characterization of bioactive lipids and the mechanisms involved in their bioactive properties impair the full exploitation of microalgae lipids. The main objectives of this thesis were to perform the identification of the lipidome of commercialized and novel microalgae using state-of-the-art lipidomic approaches based on mass spectrometry analysis, to produce and characterize lipid extracts obtained with green and sustainable approaches, to understand the plasticity of the microalgae lipidome with different cultivation conditions, and to evaluate the antioxidant and anti-inflammatory properties of microalgae lipids. To achieve these goals, we performed an identification of the fatty acid (FA) profile by gas-chromatography mass spectrometry (GC-MS), assessed the lipid quality indexes and antioxidant activity of seven different microalgae species (Chlorella vulgaris, Chlorococcum amblystomatis, Nannochloropsis oceanica, Phaeodactylum tricornutum, Scenedesmus obliquus, Spirulina sp. and Tetraselmis chui) performed the first in-depth characterization of the lipidome of two microalgae species from phylum Chlorophyta (C. amblystomatis and Tetraselmis striata) through liquid-chromatography high-resolution mass spectrometry (LC-MS), and assessed the in vitro anti-inflammatory properties of C. amblystomatis and N. oceanica lipids. The studied microalgae exhibited a species-specific FA profile and a specific n-3 PUFA composition but with species of the same phylum showing few similar tendencies. Microalgae from Chlorophyta phylum were characterized by higher amounts of α-linolenic acid (ALA), while Ochrophyta and Bacillariophyta had higher amounts of eicosapentaenoic acid (EPA). The Scenedesmus obliquus showed the highest content in n-3 PUFA while Spirulina sp. showed no content in these FA. All microalgae lipids showed low nutritional indexes revealing health-beneficial properties. The different lipid extracts showed similar antioxidant activities, with a higher activity associated with the extracts of S. obliquus and C. vulgaris. The antioxidant activity showed a positive correlation with the PUFA content. The identification of the lipidome of C. amblystomatis for the first time allowed to assign 350 polar lipid species distributed by different classes of glycolipids (GL), betaine lipids and phospholipids (PL), of which 157 were esterified to n-3 PUFA, such as α-linolenic acid (ALA) and eicosapentaenoic acid (EPA), and some previously reported with bioactive potential. Using ultrasound-assisted extraction (UAE) with ethanol (EtOH) a green solvent, we obtained food-grade extracts enriched with polar lipid-rich extracts of C. amblystomatis. Also, we obtained similar yields of extraction compared to conventional extraction methods using chlorinated solvents. Lipidomic analysis showed that lipid extracts obtained with UAE had a similar profile and yield of polar lipids rich in n-3 PUFA. The lipidome of T. striata CPT4 was also studied, and we identified 82 PL, 105 GL, 37 betaine lipids and 82 neutral lipids. Lipidomics approaches were also used to evaluate the plasticity of the lipidome with the variation of the salinity (5, 20 and 35 ppt of NaCl) and temperature (10, 20, 30 and 40°C). The different combinations of salinity and temperature allowed the production of biomass with different lipid compositions. High salinity decreased the content of GL and PL, and accumulated betaine lipids at 20°C. Higher temperatures reduced the n-3/n-6 ratio affecting nutritional properties. Finnaly, several lipid fractions of C. amblystomatis and N. oceanica enriched in GL, monogalactosyldiacylglycerol and betaine lipids and PL were obtained using solid-phase extraction and tested for anti-inflammatory activity in Raw264.7 macrophages. These lipid fractions showed strong inhibition against lipopolysaccharide (LPS)-induced production of NO and transcription of Nos2, Ptgs2, Tnfa and Il1b. The most active fractions were the betaine lipids and PL-enriched fraction from N. oceanica, and the GL-enriched fraction from C. amblystomatis. Overall, the results obtained within the scope of this thesis allowed us to significantly increase our knowledge of microalgae lipids, contributing to their valorization as ingredients, rich in potent anti-inflammatory compounds, which can be used in heathy and sustainable diets, and with the potential to prevent and resolve chronic inflammation and NCD.